Antibiotic prescription practices in six primary health centers in South Sumatra (Medical Journal of Indonesia, 2005)
Drug utilization study, especially antibiotic usage in therapy of mild acute upper respiratory infections and acute diarrheas has been conducted in six Primary Health Center (PHC) in urban, suburban and rural area in the Province of South Sumatra. We conducted systematic random sampling during which 15% of patients in each PHC were taken. We collected information about drug utilization from medical record of out patient in each PHC for three months period (January to March 1997). We recorded the characteristics of patients, the diagnosis, the number and type of drug (including injection) used. The number of cases studied was 1781, with the average number of drug per prescription being 2.7; the percentage of cases receiving an injection was 43%, and the percentage of cases receiving antibiotic was 48%. Sixty-four percent of 1277 acute respiratory tract infections (common cold), and 79% of 140 cases of acute diarrhea received antibiotic. This study showed that there is overuse or inappropriate use of drugs, especially antibiotic for acute nonspecific diarrhea and mild acute respiratory tract infections. (Med J Indones 2005; 14: 44-9) Keywords: drug utilization study, antibiotic use, acute upper respiratory infection, acute diarrhea